An empirical test for costs subadditivity in the fishery sector - Laura Onofri; Francesc Maynou (Economics and Econometrics Research Institute (EERI), 2017)
The seminal work by Baumol et al. (1982) has highlighted the importance of analyzing firms' costs structure. This allows to design proper policy measures and to understand the impacts of those policies in markets. The note presents an original method and an application for testing costs subadditivity in the fishery sector, by using a system of supply functions under strict conditions and assumptions. The method is practical, though robust, and can be applied in the absence of detailed data on costs structures. Under stringent hypothesis (that delimit the application) they can be inferred from the supply functions. Subadditivity in costs, in fact, is a more proper economic definition (and methodological approach) than traditional economies of scale in fishery. The latter, in fact, does not depend from the vessel technology, but on the degree of quantity and variety of fish species in the ocean.
Keywords: C01; C30; D24; Q22; 330; Cost subadditivity; vessel; fishery; simultaneous equations model; 2SLS